Nasikh dan Mansukh dalam Kajian Ulumul Qur'an: Analisis Metodologis dan Implikasinya terhadap Formulasi Hukum Islam - Raihana Aulia Sukhairani Suhaimi; Abu Anwar; Rika Riauwati; M. Zakariya Al Ansori; Nurin (Kartika: Jurnal Studi Keislaman, 2026)
This study examines the concepts of nasikh and mansukh as one of the fundamental themes in the discipline of Ulumul Qur'an which serves to explain the legal relationship between verses that seem to have normative differences. Although it has been discussed since the early era of the development of interpretation, this concept still raises debate because of differences in methodology in determining the existence of abrogation. This study uses a qualitative approach with an eclectic literature review method, data analysis using content analysis through a descriptive-comparative approach to examine the views of classical and contemporary scholars and analyze their implications for the formulation of Islamic law. The results of the study show that the diversity of methods based on text, history, and context can make the number of verses categorized as mansukh differ significantly between experts. Classical scholars tend to accept more cases of naskh based on the order in which the verses are descended, while contemporary scholars are more selective by prioritizing the approach of takhṣīṣ, taqyīd, and harmonization. This study also found that these differences in methodology have an impact on the variation in the determination of fatwas and legal understanding in the modern Islamic institutional environment. Therefore, this study offers a contextual-thematic interpretive framework that combines textual, historical, and maqāṣid al-shari'ah studies in order to produce a more moderate, proportionate, and relevant understanding of the nasikh-mansukh for the needs of contemporary Islamic interpretation and law